Fatigue and Health Behaviour of Ill Youth from Rural and Urban Areas - Duda, Marlena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The issue of chronic diseases in the population of children and youth should be constantly monitored due to the dynamically changing conditions of life. The risk of health deterioration and the process of convalescence are related to negative health behaviours, the feeling of fatigue and lowering quality of life. These phenomena are determined by the type of disease, individual decisions and many other factors of social nature: support, place of residence or income. The aim of this paper is to analyse the feeling of fatigue and health behaviours declared by youth in the period of late adolescence.
Keywords: a sense of fatigue; health behaviors; health; chronic illness; youth